The Functional Assessment of Chronic Illness Therapy-Fatigue Measure: Cross-Cultural Validation of an Arabic Version for Older Jordanians - Mohammad H. Abuadas; Zainab Albikawi; Osama Khoury (Iranian Journal of Nursing and Midwifery Research)
Background: Numerous national and international nursing research studies have used the 13-item Chronic Illness Therapy Functional Assessment Chronic Illness Therapy (fatigue) (FACIT‐F) scale to measure the level of self-reported fatigue among the elderly population. Nonetheless, a culturally adapted Arabic version of the scale of the same quality was required to boost its use in Arabic-speaking nations. This study cross-culturally validated the Arabic version of the FACIT-F scale and tested its validity and reliability in an Arabic-speaking population. Materials and Methods: We conducted the study among an elderly Jordanian population using a methodological cross-sectional approach. Using a cluster random selection technique, we randomly selected 250 older adults from a larger pool. We evaluated the scale’s validity, internal consistency, and acceptability. We analyzed the construct validity using both confirmatory and exploratory factor analysis. Results: The Arabic version of FACIT-F was proven to be acceptable for the one-factor model in the elderly Jordanian population. Cronbach’s alpha coefficient for the Arabic FACIT-F was 0.95, which indicated good reliability. Evidence suggested that construct validity for the FACIT-F was generally quite acceptable. Conclusions: With regard to evaluating fatigue in an older Jordanian population, the Arabic translations of the FACIT-F have been shown to be reliable and valid.